Electric-Double-Layer Coupled Oxide-Based Neuromorphic Transistors Studies - Wan, Changjin (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book focuses on essential synaptic plasticity emulations and neuromorphic computing applications realized with the aid of three-terminal synaptic devices based on ion-coupled oxide-based electric-double-layer (EDL) transistors. To replicate the robust, plastic and fault-tolerant computational power of the human brain, the emulation of essential synaptic plasticity and computation of neurons/synapse by electronic devices are generally considered to be key steps. The book shows that the formation of an EDL at the dielectric/channel interface that slightly lags behind the stimuli can be attributed to the electrostatic coupling between ions and electrons; this mechanism underlies the emulation of short-term synaptic behaviors. Furthermore, it demonstrates that electrochemical doping/dedoping processes in the semiconducting channel by penetrated ions from electrolyte can be utilized for the emulation of long-term synaptic behaviors. Lastly, it applies these synaptic transistors in an artificial visual system to demonstrate the potential for constructing neuromorphic systems. Accordingly, the book offers a unique resource on understanding the brain-machine interface, brain-like chips, artificial cognitive systems, etc. .